Family language policies: intergenerational interaction and transmission in and of language(s) and culture(s) of origin in French-speaking Africa immigrant families - Sabrina Alessandrini (University of Bologna, 2022)
Knowing the dynamics of intra-family interaction through which processes of intergenerational linguistic transmission take place is fundamental in the study of the sociolinguistic and linguistic-cultural practices within families in a permanent migratory context (Lannutti, 2010). Whatever the communication method adopted - in Italian, in language of origin, alternating codes - the language used in everyday communication between parents and children is destined to be constantly asymmetrical: different biographical and acculturation paths generate differences in linguistic repertoires, skills and uses. Through a qualitative survey (questionnaires and interviews) conducted on a sample of 27 adolescents (between 13 and 20) born in Italy from African parents, the main dynamics of interaction and linguistic and cultural transmission will be analysed.